IMPROVING THE READING NARRATIVE TEXT ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 BANGKINANG THROUGH PAIRS CHECK TECHNIQUE - Rijal, Amharu Rijal; Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This article discusses about the application of Pairs Check Technique to increase the students’ reading ability of SMAN 1 Bangkinang .It also aims to find out the factors involve in students’ improvement. Pairs Check Techinque was applied through a cycle which consist of three meetings. It was applied to 31 students of the second year students of SMAN 1 Bangkinang as the participants of the research. The data was collected by using Pre-test and Post-test including a set of observation sheets to reserve the classroom activities during the action.The result finding draws that the treatments could increase students’ reading ability in Narrative text. It was reflected by the students’ average scores which increase significantly from the Pre-test to the Post-test. Before the treatment was given, the average score of the students writing ability was 69,89. After the treatment was given for cycle, it increased to 80.65 which reach the minimum standard of English in SMAN 1 Bangkinang (80.65>75). Based on observation sheet, It was also found that the students’ average activities were 92,66. This fact answer the research---- that Pairs Check Technique can improve the student’s ability.-----Keywords: Pairs Check Technique, students’ reading ability, narrative text